2014
DOI: 10.1071/an14233
|View full text |Cite
|
Sign up to set email alerts
|

Effects of calcium salts of medium-chain fatty acids on plasma metabolite and hormone concentrations in early lactating dairy cows

Abstract: To elucidate the effects of medium-chain fatty acids (MCFA) on milk production and plasma metabolite and hormone concentrations in early lactating dairy cows, 10 multiparous Holstein dairy cows were randomly assigned to two dietary treatment groups after parturition. One group was fed a diet supplemented with calcium salts of MCFA (MCFA-Ca) for 8 weeks after parturition, while the other group was fed the same diet without the supplement (control). MCFA-Ca, containing 60% caprylic acid and 40% capric acid, was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…On the one hand, van Zijderveld et al (6) reported a greater milk fat concentration in cows receiving a diet complemented with a mixture of 8 : 0 and 10 : 0 as compared with a fat supplement rich in 16 : 0, or with PUFA from an extruded linseed product. On the other hand, Fukumori et al (40) and Sugino et al (45) observed no change on FCM or milk fat concentration and yield when diets were supplemented with Ca salts of 8 : 0 and 10 : 0 as compared with unsupplemented control.…”
Section: Discussionmentioning
confidence: 96%
“…On the one hand, van Zijderveld et al (6) reported a greater milk fat concentration in cows receiving a diet complemented with a mixture of 8 : 0 and 10 : 0 as compared with a fat supplement rich in 16 : 0, or with PUFA from an extruded linseed product. On the other hand, Fukumori et al (40) and Sugino et al (45) observed no change on FCM or milk fat concentration and yield when diets were supplemented with Ca salts of 8 : 0 and 10 : 0 as compared with unsupplemented control.…”
Section: Discussionmentioning
confidence: 96%
“…Fat is the main component of animal tissues and diets, which has very important physiological and nutritional functions. In recent years, functional fat has been studied and applied in livestock and poultry breeding (Sugino et al, 2014; Zhang et al, 2017). Medium chain triglyceride (MCT) is a salutary class of lipid, which is mainly composed of medium chain fatty acid and exists in the milk of many animals, such as rabbits, cattle, and pigs, and its antibacterial effect can be used as a substitute for antibiotics (Zentek et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…joint action of psychological, nutritional and environmental stress, it is easy to cause weaning stress of young rabbits, which is mainly reflected in diarrhea and growth retardation of young rabbits, and severe cases can lead to death of young rabbits (Skrivanova et al, 2009).…”
mentioning
confidence: 99%